PSYCHOLOGICAL ASPECTS OF THE MANIFESTATION OF MORAL FEELINGS IN EARLY ADOLESCENTS - Karimova Madina Xolmuratovna; Satieva Sholpan Serikbosynovna (American Journals Publishing, 2024)
This article shows the characteristics of early adolescence and the development of moral feelings during adolescence, as well as the analysis of the methodology of determining moral qualities in students. In our study, 30 students in early adolescence were selected as a control group and 30 adolescents as an experimental group.In the article Friedman's "What is the word good and what is the word bad?" methodology was used. The students were asked to describe a specific situation and tell how they would behave if such a situation arose, and explain why they behaved in this particular situation.After conducting the experiment, teenagers were given the task to define the concept of "ethics", and the results of this task were compared with the definitions of ethics given by the members of the control group and the experimental group. In addition, during our research, an essay on "What I like and what I don't like about the character of my classmates" was collected among early teenagers.As a result of our research, it can be observed that significant changes have occurred in the experimental group, unlike the adolescents in the control group.
Keywords: Morality, feeling, adolescence, moral virtue, value, behavior.